MoO3-rGO nanocomposites for electrochemical energy storage - Khandare, Lina; Late, Dattatray J. (Applied Surface Science, 2017)
We have synthesized the one dimensional (1D) MoO3 nanorods and MoO3-rGO nanocomposite by using sonochemical dispersion method at low temperature. The obtained products were characterized by using Raman spectroscopy, FT-IR, SEM, TEM and HR-TEM. We have demonstrated the electrochemical properties of MoO3 nanorods and MoO3-rGO nanocomposites. The specific capacitance for MoO3 nanorods and MoO3-rGO nanocomposite was calculated to be 3.3 F/g and 22.83 F/g at current density of 0.3 A/g respectively. The nanocomposite of MoO3-rGO shows the better electrochemical performance as compared to pristine MoO3 nanorods sample due to improvement in the conductivity. Our result suggests that the MoO3-rGO nanocomposites material has great potential for electrochemical energy storage and related applications. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Energy storage; Nanocomposites; Nanorods; Storage (materials); Temperature